Alu exaptation enriches the human transcriptome by introducing new gene ends - Lavi, Eitan (RNA Biol, 2018)
In mammals, transposable elements are largely silenced, but under fortuitous circumstances may be co-opted to play a functional role. Here, we show that when Alu elements are inserted within or nearby genes in sense orientation, they may contribute to the transcriptome diversity by forming new cleavage and polyadenylation sites. We mapped these new gene ends in human onto the Alu sequence and identified three hotspots of cleavage and polyadenylation site formation. Interestingly, the native Alu sequence does not contain any canonical polyadenylation signal. We therefore studied what evolutionary processes might explain the formation of these specific hotspots of novel gene ends. We show that two of the three hotspots might have emerged from mutational processes that turned sequences that resemble polyadenylation signals into full-blown canonical signals, whereas one hotspot is tightly linked to the process of Alu insertion into the genome. Overall, Alu elements may lie behind the formation of 302 new gene end variants, affecting a total of 243 genes. Intergenic Alu elements may elongate genes by creating a downstream cleavage site, intronic Alu elements may lead to gene variants which code for truncated proteins, and 3′UTR Alu elements may result in gene variants with alternative 3′UTR.